Ageisme: Narasi Ubasute dalam Film Plan 75 - Sulatri, Ni Luh Putu Ari; Purnawati, Ketut Widya; Damayanti, Silvia (Vocational College of Diponegoro University, 2023)
The story of Ubasute is an allegory presented in fiction regarding the neglect of the elderly in Japanese society. A modern variation of this story is shown in the film Plan 75, which focuses on a euthanasia program for seniors aged 75 to reduce the country's economic burden. This article examines the Ubasute narrative presented in the film Plan 75 from ageism perspective. Research data collection was carried out using the listening and note-taking methods. The descriptive analysis method is used at the data analysis stage. The results of data analysis are presented using descriptive methods. The results of the study show that the Ubasute narrative in the film Plan 75 is presented as follows: 1) Elderly people feel confused about their position in society; 2) The elderly feel embarrassed because they are a burden on their family and society; and 3) The elderly need the support of the younger generation. The Ubasute narrative shown in Plan 75 can be a medium to combat ageism, towards the elderly. The Plan 75 makes us rethink the position of the elderly in society. The elderly are not